Pengaruh Penggunaan Gawai Terhadap Produktivitas Mahasiswa Di Yogyakarta - Teguh Nugraha; Wigi Fahri Septian; Tuta Ridho Setiawan (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the effect of gadget usage on student productivity in Yogyakarta, a major educational hub in Indonesia. The increasing integration of digital devices into academic life has positioned gadgets as essential learning tools, while simultaneously introducing potential distractions that may reduce productivity. This research employed a quantitative method using a descriptive-explanatory approach. Data were collected through an online questionnaire distributed to 121 active university students in Yogyakarta using purposive sampling. Instrument validity and reliability tests were conducted, followed by classical assumption testing and linear regression analysis using SPSS version 26. The findings indicate that all measurement items are valid and reliable. The regression results show that gadget usage has a statistically measurable effect on student productivity, although its contribution is limited, suggesting that productivity is influenced by multiple interrelated factors beyond gadget usage alone. These findings emphasize that the impact of gadgets on productivity depends largely on usage patterns and self-regulation. Therefore, effective digital self-management is crucial to maximizing the academic benefits of gadget use while minimizing its disruptive effects.